ETHNOPHARMACY STUDY OF PLANTS WITH MEDICINAL PROPERTIES IN NORTH MALUKU PROVINCE - Adrias, Cici Rahmayanti; Herwin, Herwin; Jamaluddin, Jamaluddin; Kosman, Rachmat (Fakultas Farmasi, Universitas Muslim Indonesia, 2021)
North Maluku Province, especially in Joubela Village, Morotai Island Regency, South Morotai District, is one of the remote areas located in the eastern part of Indonesia. The tribes that still thrive on the island are the Galela and Tobelo, these tribes are some of the largest tribes in North Maluku, recorded to still preserve many plants as traditional medicine. The research aimed to find out the ethnopharmaceutical plants in the village of Joubela. This present study was conducted through direct observation to people who were known to understand the use of traditional medicinal plants such as shamans, community leaders and the public who have used plants for treatment which were selected through purpose sampling method. The results obtained 15 orders, 20 families, 26 genera and 26 species of plants that have empirical potential as medication and the most widely used plant as traditional medicine was garden shrub (Graptophyllum pictum L.), with the efficacy as an ulcer medicine.